Development of a Yellow Pigment Based on Bismuth and Molybdenum-Doped TiO2 for Coloring Polymers - Silva, Renata Martins da; Tebcherani, Sergio Mazurek; Kubaski, Evaldo Toniolo; Cava, Sergio; Moreira, Mario Lucio; Sequinel, Thiago [UNESP] (Wiley-Blackwell, 2015)
An inorganic yellow pigment based on TiO2 containing minor amounts of bismuth and molybdenum compounds was developed without rare earths or highly toxic elements. The material was produced starting from a composition of 99% (mol%) of rutile TiO2 and 1% of MoO3, which were previously mixed and calcined at 1200 degrees C. The composition consisted of 99.8% of the above mixture and 0.2% of bismuth(III) nitrate basic hexahydrate. This powder mixture was homogenized and calcined in a tubular furnace at 1200 degrees C, applying different heating rates: 1, 30, 40, and 60 degrees C/min. The yellow color was attributed to the presence of -Bi2O3, *-Bi2MoO6, and Bi2Ti2O7 phases. The powder particle size proved suitable for using the material as an inorganic pigment for polymers. The technological application of the pigment was tested in high-density polyethylene.